Активність ключових ферментів синтезу та розкладу проліну в проростках кукурудзи за умов засолення та обробки синтетичними регуляторами росту - Чижикова, О.А.; Палладіна, Т.О. (Видавничий дім "Академперіодика" НАН України, 2007)
The activity of pyrroline-5-carboxylate reductase (P5CR) in corn seedling roots and leaves was higher than that of proline dehydrogenase (PD). The changes of PD activity define the proline content dynamics to a great extent in roots of control and seedlings exposed to 0.1M NaCl, but it was conditioned in leaves mainly by changes of P5CR activity. The seed treatment with growth regulators — Methiur and Ivine — decreased the proline content in 8-day-old seedling tissues that occurred because its degradation was intensified in roots, and its synthesis was weakened in leaves. The proline content dynamics in corn roots was defined by changes in its degradation to a great extent and, in leaves, by changes in its synthesis under the salt stress and the preparation effect.